A86 SUBMUCOSAL INJECTION FOR POLYPECTOMY AND INTERVENTIONAL ENDOSCOPY: AN INTERNATIONAL SURVEY. (26th February 2020) - Alaoui, A; Marques, P; Djinbachian, R; Pohl, H; Libanio, D; Barkun, A N; von Renteln, D
Abstract: Background: Submucosal injection (SI) is used for standard polypectomies or during complex endoscopic interventions. SI helps to facilitate endoscopic resection and to prevent complications such as bleeding or perforation. Aims: We were interested to evaluate endoscopists practice patterns of using SI during routine standard polypectomy and complex endotherapeutic procedures. Methods: An online survey using the Google Form application was distributed through medical societies. Survey domains included training and practice characteristics of participating endoscopists as well as questions regarding the use of SI products for endoscopy procedures. Results: A total of 236 endoscopists (mainly from the US, Canada, and Europe) participated in the survey. About half (48%) of endoscopists start using SI for routine polypectomies when polyps are larger than 10 mm, while 37% of endoscopist report having a size threshold larger than 15mm for using SI (22% report using SI starting at >15 mm, and 15% report using SI starting at >20 mm). Only a minority (11%) of endoscopists report using SI for polyps <10 mm and starting SI at 6 mm. However, 30, 3% of endoscopists reported that their size threshold for using SI during polypectomies has decreased in recent years. 83% reported that using SI is beneficial for en-bloc resection, avoiding perforation (91, 5%), avoiding thermic lesions (80%) and identifying dysplastic tissue (54, 5%). Normal saline is the submucosal agent most commonly available for endoscopists (86, 4%), followed by Eleview (66, 8%), and ORISE Gel (20%). "Short lasting lift" and "cost" are reported concerns when opting for a specific SI solution. Methylene blue is the coloring agent that is most commonly used (68, 9%). Excellent submucosal elevation, availability, and length of action are the most important features an SI should have according to endoscopists' responses. Conclusions: The use of SI is common during endoscopy procedures. For standard colorectal polypectomy procedures, most endoscopists start using SI only for polyps larger than 10mm. SI is used by endoscopists to prevent complications, improve endoscopic resection and to identify dysplastic tissue. Funding Agencies: None